2011
DOI: 10.1179/1351000211y.0000000008
|View full text |Cite
|
Sign up to set email alerts
|

Metformin restores the correlation between serum-oxidized LDL and leptin levels in type 2 diabetic patients

Abstract: Metformin restores the positive correlation between serum ox-LDL and leptin levels in patients with type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 60 publications
2
8
0
Order By: Relevance
“…Consistently, serum leptin levels are lower in patients with type 1 diabetes and will increase after intensive insulin therapy [23,24]. In line with our previous studies, we showed lower serum leptin levels in patients with T2DM compared to BMI-matched, healthy controls [9]. This explains the carbohydrate craving and increased appetite of patients with uncontrolled diabetes.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistently, serum leptin levels are lower in patients with type 1 diabetes and will increase after intensive insulin therapy [23,24]. In line with our previous studies, we showed lower serum leptin levels in patients with T2DM compared to BMI-matched, healthy controls [9]. This explains the carbohydrate craving and increased appetite of patients with uncontrolled diabetes.…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, it has long been known that null mutations in genes encoding leptin and leptin receptor cause hyperphagia, severe obesity and a rise in inflammatory markers such as CRP [8]. A similar situation occurs in T2DM, with decreased leptin and increased CRP levels [9]. So we questioned why there is a positive correlation between leptin and CRP in healthy individuals [10], when they do not respond in a similar manner to chronic inflammation.…”
mentioning
confidence: 97%
“…OxLDL levels are elevated in type 2 diabetes patients and increase with duration of the disease [98]. Our results that oxLDL up-regulated the CD36 protein levels and that there was a dose-dependent relationship between degree of CD36 overexpression and resulting FITC-oxLDL accumulation suggests importance of the transporter during physiological and pathophysiological conditions.…”
Section: Paper IVmentioning
confidence: 55%
“…The effect of oxLDL in development of diabetes is however largely unknown. Patients with type 2 diabetes have been found to have higher levels of serum oxLDL than controls and these levels increased with duration of type 2 diabetes [98]. LDL was found to be taken up by rat and human beta cells [99] via an LDL receptor [100].…”
Section: Fatty Acid and Lipoprotein Interaction With Beta Cells Undermentioning
confidence: 98%
“…Although uncommon, hypoglycemia potentially can occur with a significant caloric deficit, especially during strenuous exercise and using the drug concurrently with other glucose-lowering agents, such as sulfonylureas and ethanol (U.S. FDA, 2008). In relation to cardiovascular effects, metformin also reduces plasma lipids, such as triglycerides and low density lipoprotein (LDL) cholesterol levels (Nakhjavani et al, 2011), but consistent cardiovascular benefits (e.g., myocardial infarction, stroke, etc.) from clinical trials have not been robust (Asche, Hippler, & Eurich, 2014).…”
Section: In Summarymentioning
confidence: 99%